2017
DOI: 10.4149/bll_2017_015
|View full text |Cite
|
Sign up to set email alerts
|

Plasma nesfatin 1 level in patients with first attack psychosis

Abstract: OBJECTIVES: This study aimed to investigate the possible relationship between plasma concentrations of nesfatin 1 and fi rst attack psychosis. METHODS: Totally, 32 patients with the fi rst episode psychosis and 33 randomly selected weight-and body mass index-matched healthy volunteers admitted to Mustafa Kemal University, Faculty of Medicine, Training and Research Hospital, Psychiatry outpatient clinic were included. Healthy control subjects were matched in terms of weight and body mass index (BMI). The Positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Nesfatin-1, a novel satiety molecule, has been reported to be involved in a variety of affective disorders, including anxiety disorder, 24 depression, 13 and psychosis. 25 Clinical studies have shown that the average nesfatin-1 level in MDD patients is statistically higher than that in the control group. 12 Similarly, plasma nesfatin-1 levels were also increased in rat subjected to avoiding stress, an acute depression model.…”
Section: Discussionmentioning
confidence: 99%
“…Nesfatin-1, a novel satiety molecule, has been reported to be involved in a variety of affective disorders, including anxiety disorder, 24 depression, 13 and psychosis. 25 Clinical studies have shown that the average nesfatin-1 level in MDD patients is statistically higher than that in the control group. 12 Similarly, plasma nesfatin-1 levels were also increased in rat subjected to avoiding stress, an acute depression model.…”
Section: Discussionmentioning
confidence: 99%
“… 71 These immunological changes include high concentrations of pro-inflammatory cytokines and chemokines in the circulation and cerebrospinal fluid, as well as changes in immune cell function in the central nervous system. 72 , 73 Adipose tissue directly or indirectly secretes pro-inflammatory cytokines and proteins (IL-6, TNF-α, insulin-like growth factor-1, leptin, resistin, apelin, visfatin, CCL22, and nesfatin-1), 30 , 31 , 33 , 74 and patients with schizophrenia also show activation of microglia, which contributes to the high serum concentrations of pro-inflammatory cytokines. 73 , 75 Some of these substances are present and/or have receptors in parts of the central nervous system, but their exact roles in the pathophysiology of psychosis are still being studied.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Several previous studies have demonstrated that high circulating concentrations of these substances are present in patients with psychotic disorders, both during the early and later phases. 30 , 31 , 33 Several types of adipokine receptors have been identified in components of the central nervous system and have been demonstrated to affect brain function. 34 This provides an important link between obesity/MetS and psychotic disorders, namely greater monocyte/macrophage activation and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Nesfatin-1, another new anorexigenic peptide hormone, plays an important role in the integration of food intake, energy expenditure, and glucose homeostasis (9). In the past decade, nesfatin-1 has been found to be involved in a variety of affective disorders, including anxiety disorder (10), depression (11), and psychosis (12). However, no studies on the relationship between nesfatin-1 in AD and craving have been conducted.…”
Section: Introductionmentioning
confidence: 99%